The socio-economic power of renewable energy production cooperatives in Germany: Results of an empirical assessment - Sarah Debor (Wuppertal Institut für Klima, Umwelt, Energie, 2014)
This paper reflects the socio-economic power of renewable energy production cooperatives for a wider energy system transformation in Germany. Energy cooperatives have turned into important supporters of renewable and decentralised energy structures, due to their strong growth since the year 2006, their participation in local renewable energy projects and their democratic awareness. The cooperative form of coordinating regional energy projects applies to a decentralised energy system that is managed by many smaller firms - a system concept that is preferred by the majority of German citizens. However, there is not enough knowledge to understand to what extent this organisational form is able to unify a broad group of actors in promoting a renewable energy system (societal power) and to gather capital for elaborating renewable energy supply structures (economic power). The reflection is based on an empirical assessment of all energy cooperatives that were registered in Germany by 31st December 2013. Their growth dynamic and their business approaches are discussed. A special focus lies on renewable energy production cooperatives. The study presents the development of their members, their capital, their profit and loss, as well as their investment intensity over a timeframe of three years (2010-2012). The socio-economic potential of renewable energy production cooperatives for supporting a renewable energy system is discussed against the background of empirical results. – – Das Diskussionspapier reflektiert die sozio-ökonomische Macht erneuerbarer Energieproduktions-Genossenschaften für eine Energiewende in Deutschland. Energiegenossenschaften sind durch ihr starkes Wachstum seit dem Jahr 2006, ihre Beteiligung an lokalen Energieprojekten, sowie ihrem demokratischen Selbstverständnis zu wichtigen Unterstützern von erneuerbaren und dezentralen Energiestrukturen geworden. Die Koordinierung lokaler Energieprojekte durch Genossenschaften steht für ein dezentrales Energiesystem, das vor allem von vielen kleineren Unternehmen verwaltet wird - ein Systemkonzept, das von einer Mehrheit in Deutschland bevorzugt wird. Allerdings existieren nicht genug Kenntnisse über das Vermögen dieser Organisationsform, viele Akteure für die Förderung eines erneuerbaren Energiesystems zu vereinen (gesellschaftliche Macht), sowie Kapital für die Diffusion erneuerbarer Energieversorgungsstrukturen zu sammeln (wirtschaftliche Macht). Die Reflektion basiert auf einer empirischen Untersuchung aller Energiegenossenschaften, die in Deutschland bis zum 31. Dezember 2013 registriert wurden. Ihre Wachstumsdynamik und Geschäftsansätze werden vorgestellt. Der Schwerpunkt der Analyse liegt auf erneuerbaren Energieproduktions-Genossenschaften. Die Studie beschreibt die Entwicklung ihrer Mitglieder und des Kapitals, sowie ihre Investitionsintensität für einen Zeitraum von drei Jahren (2010-2012). Das sozio-ökonomische Potenzial von Energiegenossenschaften für die Unterstützung eines erneuerbaren Energiesystems wird vor dem Hintergrund der empirischen Ergebnisse diskutiert.
urn:nbn:de:bsz:wup4-opus-53644
Keywords: 330